2015
DOI: 10.1371/journal.pone.0145433
|View full text |Cite
|
Sign up to set email alerts
|

Reintroduction of the European Capercaillie from the Capercaillie Breeding Centre in Wisła Forest District: Genetic Assessments of Captive and Reintroduced Populations

Abstract: The Western capercaillie (Tetrao urogallus) is a specific bird species, which, despite its very broad distribution and large global population size, is highly endangered in many Western and Central European countries. According to the species situation, in many countries (including Poland), breeding and reintroduction programmes have been started. One of the most complex and large-scale reintroduction programmes was started in Bory Dolnośląskie Forest, and the Capercaillie Breeding Centre in Wisła Forest Distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 42 publications
1
17
0
4
Order By: Relevance
“…Despite the breeding isolation of these two lines in the breeding programme pursued at the Wisła centre, we detected the presence of a few individuals of mixed origin. Therefore we suggest there may be inaccuracies between the breeding documentation and pedigree genetic data or wrong assignment of founder individuals to genetic lineages [82]. We speculate that we can no longer assume isolation between breeding lines.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the breeding isolation of these two lines in the breeding programme pursued at the Wisła centre, we detected the presence of a few individuals of mixed origin. Therefore we suggest there may be inaccuracies between the breeding documentation and pedigree genetic data or wrong assignment of founder individuals to genetic lineages [82]. We speculate that we can no longer assume isolation between breeding lines.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic aspects influence not only the short-term reintroduction success (due to the genetic architecture of the founder individuals), but also the long-term reintroduction success (due to adaptive evolutionary potential and inbreeding). Several studies identified genetic consequences imposed by reintroductions based on microsatellite loci (e.g., Biebach & Keller, 2009;Diefenbach, Hansen, Bohling, & Miller Butterworth, 2015;Jamieson, 2011;Strzała, Kowalczyk, & Łukaszewicz, 2015), but only very few studies surveyed genomewide effects or monitored long-term consequences.…”
mentioning
confidence: 99%
“…Według ostatnich danych, w Polsce istnieją cztery lokalne populacje w dużych kompleksach leśnych, spełniających wymagania siedliskowe gatunku. Najwięcej osobników zamieszkuje lasy górskie Beskidu Śląskiego i Żywieckiego, druga pod względem liczebności populacja zlokalizowana jest na Lubelszczyźnie w Lasach Janowskich, a najmniej liczne są ostoje w Puszczy Solskiej i Augustowskiej (13,14,19). Aktualnie głu-szec na terenie całego kraju objęty jest ścisłą ochroną gatunkową, pomimo której wciąż obserwowany jest spadek jego liczebności.…”
Section: Occurrence Of Dispersive Stages Of Endoparasites In the Faecunclassified
“…Biorąc pod uwagę unikatową specyfikę hodowli głuszców, realne wydaje się również zagrożenie inwazjologiczne ze strony ptactwa przebywającego w otoczeniu wolier hodowlanych i adaptacyjnych, które organizuje się w warunkach zbliżonych do naturalnego środowiska, na ograniczonych siatką terenach leśnych (9,19,21). W miejscach tych głuszce narażone są na kontakt z formami dyspersyjnymi pasożytów, rozsiewanych przez przebywające w pobliżu wolier dzikie ptaki.…”
Section: Ryc 3 Jaja C Caundinflata Z Kału Głuszca (Zdjęcie Z Mikrounclassified